2021
DOI: 10.1021/acs.jafc.1c03532
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profile and Biosynthesis of Post-harvest Apples are Affected by the Mechanical Damage

Abstract: Mechanical damage to fruit causes flavor changes during post-harvest supply chains. It is important to identify the main volatiles and explore their biosynthesis mechanism. In this study, the volatile changes in apples caused by mechanical damage were analyzed by gas chromatography−ion mobility spectrometry. Hexanal and ethyl acetate were accumulated and identified as potential volatile biomarkers to detect damaged apples. The study on the lipoxygenase (LOX) pathway and transcription factors (TFs) shows that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In particular, the relative contents of ethyl acetate and D-limonene were found to be increased with the increase of storage time after impact damage. Our previous research also found that the relative content of ethyl acetate in yellow peaches [39] and apples [42] was increased after being subjected to compression damage. It is proposed that ethyl acetate can be considered a potential volatile biomarker to detect damaged apples [42].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, the relative contents of ethyl acetate and D-limonene were found to be increased with the increase of storage time after impact damage. Our previous research also found that the relative content of ethyl acetate in yellow peaches [39] and apples [42] was increased after being subjected to compression damage. It is proposed that ethyl acetate can be considered a potential volatile biomarker to detect damaged apples [42].…”
Section: Discussionmentioning
confidence: 61%
“…Our previous research also found that the relative content of ethyl acetate in yellow peaches [39] and apples [42] was increased after being subjected to compression damage. It is proposed that ethyl acetate can be considered a potential volatile biomarker to detect damaged apples [42]. Regarding D-limonene, Chalupowicz et al [43] indicated that limonene was a promising biomarker for the pathogen activity of citrus.…”
Section: Discussionmentioning
confidence: 61%
“…By comparing aromatic compounds present in grapevine berry development, it was found that lipoxygenase-hydroperoxides lyase (LOX-HPL) pathway-related genes were associated with the accumulation of hexanal, while VvLOXA may be a crucial gene in the regulation of C6 volatiles synthesis [ 9 ]. During transport of apples, transcription factors (TFs) may lead to hexanal accumulation by regulating the expression of genes related to the LOX pathway [ 10 ]. The gas chromatography-mass spectrometry (GC-MS) technique was applied to identify hexanal as the characteristic compound in the Great River black pig dry cured ham, which was determined to be derived from the oxidation of fatty acids and the degradation of amino acids, but the specific gene involved was not identified [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of HS‐GC‐IMS over other similar techniques are that it can work under normal pressure, does not complex require sample pretreatment, and has a short analysis time and low detection threshold (Rodríguez‐Maecker et al., 2017). HS‐GC‐IMS analysis has been extensively applied to food materials, including white bread (Pu et al., 2019), olive oil (Garrido‐Delgado et al., 2015), dry‐cured fish (Q. Zhang et al., 2020), raspberry wines (H. M. Li et al., 2020), apple (Lin et al., 2021), and jujube fruit (X. Sun et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…HS-GC-IMS analysis has been extensively applied to food materials, including white bread (Pu et al, 2019), olive oil (Garrido-Delgado et al, 2015), dry-cured fish (Q. Zhang et al, 2020), raspberry wines (H. M. Li et al, 2020), apple (Lin et al, 2021), and jujube fruit (X. Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%